The economics of adaptation to climate change - the case of Germany - Dannenberg, Astrid; Mennel, Tim; Osberghaus, Daniel; Sturm, Bodo (Mannheim, 2009)
"Germany still has a generous pay-as-you-go public pension insurance with high effective replacement rates and low effective retirement ages. Nevertheless, through a long reform process that began in 1992, the paradigm of public pension provision has radically changed in response to the country's looming ageing crisis. In a nutshell, the path to improved public pension finances in Germany might be best described as a move from a defined benefit scheme to a defined contribution scheme. After the last major amendment in 2007 that will lift the statutory retirement age to 67 the debate about further pension reform measures basically had come to a stop. The current crisis in the financial sector, however, has brought the pension system in Germany under political pressure again. Against this background, this article provides a synthetic overview of the recent developments in the German pension system and their impact on current and future pension finances. We point to new threats to sustainable public pension finances developing in the wake of the financial crisis: First, pressure to disconnect the annual adjustment of pensions from annual growth of wages, as average wage earnings are predicted to decline. Yet a ban on nominal pension cuts is at odds with the guiding principle of the last pension reforms in Germany, namely to reduce the replacement rate. Second, pressure to moderate the scheduled increase in mandatory retirement age, as employment opportunities are worsening also for older workers. However, it is wrong to adapt the long-term mandatory retirement age reform in view of short-term economic fluctuations. It is designed to unfold very gradually, such that it leaves the actors on the labour market with enough time to adapt to new structural conditions. In the current situation of economic turmoil, the core challenge at present is to protect what has been accomplished with regards to long-term financial sustainability against demands from the public to soften the reforms. Still in the next period of calmer economic waters, pension reformers should tackle pending issues. A first issue is integration of the East and West German public pension schemes. A second, more important issue is provision of pension income for the low-skilled, as the growing second pension pillar does not well reach the poor."